Wacana Masyarakat Madani: Dialektika Islam dengan Problem Kebangsaan - Mohammad Muslih (TSAQAFAH, 2010)
This article contributes to the analysis of the “madani society” discourse and its development in Indonesia as a form of a struggle and dialectic of intellectual Muslim to interpret Islamic teachings in its relationship to modern life, especially to politics and nationality problems. The Islamic basic concept about the democratic principles such as justice, equality, freedom and deliberation, including the attitudes of tolerance and recognition of human rights actually had been developed well over the Apostles and the Khilafat ‘al-Rashidin political and social life. This Islamic political concept is tried to be reconstructed back by Muslim intellectuals with the idea of madani community. The presence of this discourse in Indonesia seems externally to be affected by the discourse of civil society that had been becoming a global currents of thought since the 1990s, and internally cannot be separated from the condition of the nation at that time, especially the unavailability of public space, besides as the impact of the model static approach developed in the New Order political reality.